(untitled) (International Journal of Innovative Technologies in Economy, 2019)
This paper contribute to the forecasted total budget revenues in Uzbekistan. It is aim to investigate long run and short run relationship between number of registered company, total number of taxpayers and forecasted total budget revenues from 1998 and 2017. More specifically, this dynamic relationship using bounds testing approach to co integration and the ARDL model. The main empirical findings indicate the existence of directional relationship between the number of registered company and forecasted total budget revenues in short run and long run. This mean that increase the number of registered company leads to go up forecasted total budget revenues. However, a unidirectional relationship between the total number of taxpayers and forecasted total budget revenues are confirmed in the long run and short run.